Reliability of the Shuttle Walk Test With Controlled Incremental Velocity in Patients With Difficult-to-Control Asthma. Issue 1 (January 2018) - Costa, Ivan Peres; Dal Corso, Simone; Borghi-Silva, Audrey; Peixoto, Fabiana; Stirbulov, Roberto; Arena, Ross; Cahalin, Lawrence P.; Malosá Sampaio, Luciana Maria
Abstract : Purpose: Asthma is a chronic inflammatory condition characterized by bronchial hypersensitivity to endogenous or exogenous agents and variable airflow limitation, which is reversible either spontaneously or with the use of medication. The evaluation of functional capacity in these patients is commonly performed using field tests to gauge activity of daily living. However, the reliability of the symptom-controlled shuttle walk test has not yet been determined for individuals with difficult-to-control asthma. The aim of the present study was to determine the reliability of the shuttle walk test in patients with severe, difficult-to-control asthma. Methods: Forty-five patients were evaluated including lung function tests, the International Physical Activity Questionnaire (IPAQ), and the Asthma Control Questionnaire. The participants performed a shuttle walk test twice, with a 20-min rest period between tests. Results: The mean distance walked for this cohort was 330.5 m (range, 50-570 m) on the first walk test and 336.3 m (range, 60-571 m) on the second test. There was no statistical difference between the mean distances walked. The Bland-Altman plots of the 2 tests revealed a mean difference of −12.7 m, with a 95% CI of 37.9 to −63.2 m. Significant correlations were found between the distance walked in meters and the IPAQ ( r = 0.36, P < .01) and distance in meters and muscle mass ( r = 0.39, P < .009). Conclusion: The shuttle walk test is reliable for individuals with difficult-to-control asthma and can be used in the evaluation of functional capacity. Abstract : Forty-five difficult-to-control asthmatic patients were evaluated to determine the reliability of the shuttle walk test, performed twice with a 20-min rest period between tests. The shuttle walk test proved to be reliable for individuals with difficult-to-control asthma and can be used in the evaluation of functional capacity.